Japan's Response to AUKUS in Suppressing China's Rise - Larasati, Larasati; Amalia, Ridha (Vox Populi, 2025)
This article aims to examine the reasons behind Japan’s ambiguous stance regarding its potential membership in the AUKUS defence pact. Japan’s membership in AUKUS has become increasingly urgent as its role is deemed necessary in supporting Pillar II of AUKUS, which focuses on cybersecurity, artificial intelligence, quantum technology, and additional underwater capabilities. Another consideration for Japan’s membership is the phenomenon of China’s rise, which AUKUS partners perceive as a security threat. Japan’s inclusion is expected to help counter China’s influence in the Indo-Pacific region. Japan’s membership is highly anticipated, as it is considered a like-minded country and a close ally of the United States. In theory, Japan should not face difficulties in making its membership decision, especially since AUKUS partners strongly support its inclusion. However, despite official statements from the Japanese government indicating openness and a positive reception toward the opportunity, Japan has yet to make a definitive decision regarding its AUKUS membership. This article seeks to understand why Japan remains uncertain (ambiguous) about its membership in AUKUS. This question is addressed through the concept of defensive realism. Based on this approach, Japan prioritizes its national interests by not joining AUKUS while still supporting the alliance’s continuity. This stance allows Japan to maintain cooperation with AUKUS partners without becoming an official member of the alliance. It also reflects Japan’s strategy in maintaining regional balance, ensuring that its position does not excessively escalate tensions with China, which is a global powerhouse in the region.